KONTRIBUSI USAHATANI KANGKUNG AIR TERHADAP PENDAPATAN KELUARAGA PETANI DI KELURAHAN MAHENA KECAMATAN TAHUNA - Okteven Senggasi; Vicky R.B. Moniaga; Agnes E. Loho; Celsius Talumingan (COCOS, 2014)
ABSTRAKThe Objective of this research is to determine the contribution of water spinach to the household income of farmer in village Tahuna Sub District. Primary data obtained through interviews with farmers techniques based on a list of questions while the secondary data obtained from relevant agencies such as office of Tahuna Sub District. The determination of research location isData obtained in this study and the data were analyzed by descriptive proceed with spinach water farm income and farm family income.The results of this research indicated that the mounthy average revenue of water spinach farmer in was Rp.4.669.090 and the mounthly average cost during the production was Rp.239.000 obtained from the total fixed costs plus total variable costs. So that the mounthly average income was Rp.4.430.090The average income outside the water spinacth farmwasRp.335.454 and the average income of other family members was Rp.81.818The contribution of water spinach to the total of household income was 91,4 percent. There here water spinac has a great countribution to the is total income of household.